Morphometrical analysis of cleaning capacity of a hybrid instrumentation in mesial flattened root canals - Oliveira Goncalves, Leonardo Cantanhede; Sponchiado Junior, Emilio Carlos; da Frota, Matheus Franco [UNESP]; Franco Marques, Andre Augusto; Roberti Garcia, Lucas da Fonseca (Wiley-Blackwell, 2011)
The cleaning capacity of hybrid and rotary instrumentation techniques in mesial flattened canals of mandibular first molars was evaluated by morphometrical analysis in this study. Twenty human mandibular first molars were randomly assigned into two groups, according to instrumentation technique, as follows: group 1, instrumentation with ProTaper Starter Kit (Dentsply/Maillefer) rotary system; group 2, manual instrumentation using K files (Dentsply/Maillefer) by crown-down technique in middle and apical thirds, cervical preparation with Gates-Glidden #1 and #2 (Dentsply/Maillefer) burs, and to finalise the preparation, ProTaper F2 and F3 rotary files. Serial transverse cross-sections (5 mu m) of the apical third, stained with hematoxylin and eosin, were analysed at 100 x original magnification. The images were submitted to morphometrical analysis with an integration grid to determine the percentage of root canal area with debris. Statiscal analysis (t-Student, P < 0.05) showed significant difference between the techniques (P < 0.05), although neither completely cleaned the root canal.
Keywords: cleaning; endodontics; flattened root canals; Ni-Ti files; rotary instrumentation